Global attractors for Moore–Gibson–Thompson thermoelastic extensible beams and Berger plates - Dell'Oro, Filippo; Liverani, Lorenzo; Pata, Vittorino; Quintanilla, Ramon (Nonlinear Analysis-Real World Applications, 2025)
For p∈R, and α,β,γ,δ,η>0, we consider an abstract version of the system utt+Δ2u−(p+‖∇u‖2)Δu=ηΔ(ϕtt+αϕt)+f ϕttt+αϕtt−βΔϕt−γΔϕ−δΔϕtt=−ηΔut describing the dynamics of thermoelastic extensible beams or Berger plates, where the evolution of the temperature is ruled by a regularized Moore–Gibson–Thompson type equation. The existence of a global attractor of optimal regularity is proved.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Absorbing set; Exponential decay; Global attractor; MGT heat conduction; Thermoelastic extensible beams and Berger plates